2015
DOI: 10.4166/kjg.2015.65.4.252
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Pancreatic Abscess Mimicking Pancreatic Neoplasm: A Four-Case Series

Abstract: A pyogenic pancreatic abscess mimicking pancreatic neoplasm in the absence of acute pancreatitis is rare. We report four patients who each presented with a pancreatic mass at the pancreas head or body without acute pancreatitis. The presenting symptoms were abdominal pain, fever, or weight loss. Abdominal CT scans showed low-density round masses at the pancreas head or body with/without lymphadenopathy. In each case, a PET-CT scan showed a mass with a high SUV, indicating possible malignancy. Comorbid diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Kim et al reported four cases of pancreatic abscess; three patients had diabetes, and three had a normal blood CA 19-9 level. 7 A pancreatic abscess without fever and an elevated leukocyte count but with diabetes has been rarely reported. Our case was rare in that the patient just had an elevated CA 19-9 level.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported four cases of pancreatic abscess; three patients had diabetes, and three had a normal blood CA 19-9 level. 7 A pancreatic abscess without fever and an elevated leukocyte count but with diabetes has been rarely reported. Our case was rare in that the patient just had an elevated CA 19-9 level.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports on pancreatic abscesses (infected pancreatic necrosis) have been published that would come close to misdiagnosis as malignancy. These lesions were finally diagnosed based on diagnostic laparoscopy, CT-guided percutaneous aspiration, and EUS-FNA (Table 1) [5][6][7][8]. Among these modalities, EUS with FNA has an advantage because it is less invasive in diagnosing pancreatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, preoperative contrastenhanced endoscopic ultrasonography (EUS) has been reported to be very useful for the diagnosis of pancreatic disorders. 14 In addition, EUS-guided fine needle aspiration cytology has proved to be very sensitive and specific for a cystic pancreatic lesion. 15 In our centre, the EUS is not available.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Extension of the abscess from nearby anatomic structures, hematogenous spread from a distant focus of infection, or lymphatic spread from the intestinal tract, are other possible causes for pancreatic abscesses having no history of acute pancreatitis. 14,21 Streptococcus anginosus group, as part of the normal gastrointestinal flora, it is rarely implicated in disseminated infections originating from colon diseases. 12,22 Nevertheless, there are reports that describe an association between Streptococcus anginosus infection and colorectal, oesophageal, gastric cancers and endocarditis.…”
Section: Discussionmentioning
confidence: 99%